Cooperation and cognition in wireless communication systems for spectrum efficiency enhancement - Yang, Han (2011)
The explosive growth of wireless applications and steadily increasing demands for higher quality of service have led to a perceived dearth of available radio bandwidth, which necessitates a more efficient utilization of spectrum resources. Both cooperation and cognition in wireless networks have individually been shown to be powerful tools to achieve such a purpose. The objective of this dissertation is to jointly investigate these two techniques and propose practical protocols for spectrum efficiency enhancement in wireless networks.